NILAI DIAGNOSTIK KASET IMUNOKROMATOGRAFI SEBAGAI ALAT PENUNJANG DIAGNOSIS DEMAM BERDARAH DENGUE PADA PENDERITA DEWASA - Kusuma Pindayani; Aryati Aryati; Y. Probohoesodo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
A rapid immunochromatographic test that incorporates blue particle conjugated with recombinant dengue envelope protein,antihuman IgM monoclonal antibodies and antihuman IgG monoclonal antibodies (Virotec Dengue IgG/IgM XP; Indec Diagnostics,Indonesia using technology of USA) was evaluated by using IgG and IgM captured ELISA (Dengue Duo ELISA, Panbio) which has a99% sensitivity and a 92% specificity as the “gold standard”. This assay, cassette in shape, is performed in 15–30 minutes and detectsboth immunoglobulin M (IgM) and IgG in a capture format. There were 57 paired sera of dengue haemmorhagic fever (according toWHO 1997 criterias) and 72 sera of non dengue haemmorhagic fever patients (typhoid fever, UTI, malaria, chikungunya, hepatitis andpneumonia). For the diagnosis of dengue virus infection, the rapid test showed a sensitivity of 98%, positive predictive value of 88%,negative predictive value of 98% and specificity of 99%. The rapid test is a useful aid in rapid diagnosis and differentiation betweenprimary and secondary dengue virus infection.